KEMAMPUAN MEMBACA PEMAHAMAN DALAM PENGEMBANGAN ANAK - ANWAR, KHAIRIL (JURNAL PENDIDIKAN DASAR, 2012)
Reading comprehension can be defined as a readiness of active thought process of a reader who deliberately construct meaning in the form of an understanding of the concepts and more in-depth information presented in text form. Reading comprehension, requires the reader to use the information they have to filter, interpret, organize, and reflect on the information coming from each page. Efficient interpretation of the text include a mixture of word comprehension skills, relations major new information to knowledge, and the application of appropriate strategies such as placing the main idea, making connections, questioning, infer and predict. Finding the main idea is integral to reading comprehension and often have a challenge to the efforts of the readers. Teaching reading to mengidentifikasiide main ideas in the text as a promising approach a positive impact on reading comprehension skills. In addition, the conclusion was able to build awareness of the value of the main ideas in the text. Exercise can replace concluded reading comprehension when direct teaching approach used to teach the technique, when students enough time to apply the technique, and when the special instruction on how to change the strategy supported for new materials.Keywords: Reading, Understanding, Teaching, Interpreting